STUDI EKSPERIMEN PENGARUH PENGGUNAAN ENDPLATE BERLUBANG PADA TURBIN SAVONIUS - Zain Lillahulhaq; Ilmiatul Masfufiah; Irsyad Amirullah (Scientific Journal of Mechanical Engineering Kinematika, 2022)
The Savonius turbine is widely used because it has a simple design. However, the Savonius turbine has a lower efficiency than the Horizontal Axis Wind Turbine (HAWT). Several studies have been conducted to increase the efficiency of the Savonius turbine. Turbine performance can be improved by reducing the negative vortex by creating a flushing effect. This experiment was conducted to determine the impact of circular cut-off end plates on the Savonius turbine. The research results are shown through turbine performance data on wind turbine angular speed, electric power, static torque, and efficiency. The wind turbines with circular cut-off endplates had higher angular velocities than conventional Savonius turbines. The angular velocity measurement is carried out when the turbine is unloading. Meanwhile, the electric power and static torque of a conventional turbine are more significant than a modified turbine. The measurement of electric power and static torque is carried out when the turbine is in a generator-loaded condition (loading).